Investigation of microstructural, mechanical, and electrical characteristics of CuNi5W alloy synthesized by warm compaction - Agung Ardiansyah; Bagus Prasetiyo; Suprianto Suprianto; Irfan Sitorus (Politeknik Negeri Lhokseumawe, 2025)
In the Electric Discharge Machining (EDM) process, electrode materials require high electrical conductivity and sufficient mechanical strength. These electrodes can be fabricated by the Powder Metallurgy (PM) technique from copper-based alloys. The electrode strength can be improved by adding refractory materials through a properly selected warm compaction parameter, such as temperature and pressure compaction. The study focused on analyzing microstructural changes, compressive strength, hardness, and electrical behavior of the alloy. High-purity (Cu, Ni, W) elements were synthesized by warm compaction with different penetration loads and temperatures to produce CuNi5W alloys. The physical, mechanical, and electrical testing were carried out at room temperature. The results indicate that incorporating tungsten (W) into Cu-Ni-based alloys, combined with higher compaction temperatures and pressures during warm compaction, leads to an improvement in density, hardness, and electrical conductivity. The optimum values for these properties were achieved in the Cu-Ni-W-based alloy compacted at 250Â°C and 250â€¯MPa. The CuNi5W alloys exhibited a microstructure characterized by a solid solution matrix in which tungsten particles were evenly distributed, playing a key role in enhancing the hardness of the model CuNi5W-based alloy.